Infrared Studies on Surgically Removed Urinary Stones - Rao, T.V.R.K.; Das, Maitreyee (Asian Journal of Chemistry, 2010)
Surgically removed urinary stones were procured from the local nursing homes. The stones were analyzed qualitatively for their mineral constituents. Thirty five stone samples, containing oxalate or phosphate or both, were selected for study. Infrared spectra of the selected stone samples were recorded in the range of 4000-500 cm-1 in KBr phase. Phosphate and oxalate bands were studied. Results revealed the presence of bridging and coordinating mode of oxalate and coordinating mode of phosphate in the stones. Water molecules in the stones have also been evidenced to be in the coordinated mode. Bonding of phosphate and oxalate groups in the urinary stones has been discussed in the light of the infrared data.